2019
DOI: 10.3390/f10121108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Duration of Microwave Irradiation of Scots Pine (Pinus sylvestris L.) Cones on the Quality of Harvested Seeds

Abstract: To improve the process of seed extraction, new solutions have been investigated in an attempt to develop guidelines for the construction of small seed extraction equipment. One of the solutions proposed in this field is the use of electromagnetic radiation in the first stage of hulling cones, reducing their initial moisture content, which will result in quicker scale opening. It is proposed that cones should be irradiated for a relatively short period in the first stage. This operation will allow a quicker los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The results of this study showed that germination rates decline with increase in exposure period within the three phases of extraction. Earlier studies by [24] showed that exposure to higher seed extraction temperatures negatively influence germination of pine seeds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this study showed that germination rates decline with increase in exposure period within the three phases of extraction. Earlier studies by [24] showed that exposure to higher seed extraction temperatures negatively influence germination of pine seeds.…”
Section: Discussionmentioning
confidence: 98%
“…Higher temperature intensities (a function of the temperature reached and the time of exposure) has been shown to be a key factor in cone opening for seed release and also influences seed germination energy, rate and capacity [23][24][25][26]. Heat tolerance and thermal shock resistance as indicated by germination energy is shown to be dependent on species, cone and seed moisture content [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The seeds have great importance at this point. In this regard, experiments in Pinus sylvestrys have been carried out to evaluate the effect of humidity reduction on the quality of seeds obtained from cones in order to observe a faster and more intensive scale opening of cone scales [23]. Research has also been initiated on the performance of seedlings from color-sorted seeds of Scots pine [24].…”
Section: Ecological and Economic Importance Of Conifersmentioning
confidence: 99%
“…However, to our knowledge, the initial opening event of a cone has not been documented from a biomechanical viewpoint in detail until now. A study by Aniszewska et al (2019) has shown that short microwave irradiation of initially closed Scots pine cones leads to their opening due to the rapid loss of moisture, and that viable seeds can be harvested from them. The process of initial opening is ecologically relevant, as it influences the dispersal of the mostly airborne seeds and, ultimately, the survival rate of seedlings (Winsa, 1995;Przybylski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, the initial opening event of a cone has not been documented from a biomechanical viewpoint in detail until now. A study by Aniszewska et al. (2019) has shown that short microwave irradiation of initially closed Scots pine cones leads to their opening due to the rapid loss of moisture, and that viable seeds can be harvested from them.…”
Section: Introductionmentioning
confidence: 99%